Enhancement of adipose stem cell quality via Cu‐MON: Transcriptome and bioinformatics analysis of normal and diabetic stem cells - Ruixin Pang; Kaijing Liu; Biou Liu; Jing Yang (FASEB BioAdvances, 2025)
Abstract Transplanted adipose stem cells (ASC) have a low survival rate in the body, and there are not many ASC that can be effectively used, which weakens their tissue repair function. Based on this status quo, a new type of copper‐based metal–organic network (Cu‐MON) was used to pretreat cells to regulate cell activity in order to improve the efficacy of cell therapy or reduce the number of cells used, thus reducing the cost of clinical treatment. Gene expression changes before and after Cu‐MON treatment of normal donor adipose stem cells (ND‐ASC) and type 2 diabetes mellitus adipose stem cells (T2DM‐ASC) were evaluated through RNA sequencing, KEGG and GO enrichment analysis. The results showed that Cu‐MON improved ASC cell quality by regulating immune response and promoting paracrine secretion. IL‐17 signaling pathway and IL‐6, CXCL8, and MMP‐9 were key pathways and necessary genes that affected the ability of stem cells. In addition, Cu‐MON also improved stem cell antiviral ability through Type I interferon signaling pathway. Our research showed that Cu‐MON had improved the cell quality of ASC by regulating immune response, promoting paracrine secretion, and improving antiviral capabilities. This approach to biomaterial pretreatment is fast, convenient, and relatively safe, and provides new strategies for improving the efficiency of cell therapies.